PHYSICS NOBEL LAUREATE WOLFGANG KETTERLE: A SCIENTOMETRIC PORTRAIT - Koganuramah, M.M.; Angadi, Mallikarjun; Kademani, B. S.; Kalyane, V. L.; Jange, Suresh (Malaysian Journal of Library and Information Science, 2004)
Wolfgang Ketterle was honoured with the Nobel Prize in Physics (2001) at 44 years of biological age and at 20 years of research publishing career. He had 115 publications during 1982 – 2002 in domains: Bose-Einstein Condensation (68), Laser Spectroscopy (30), and Atomic Physics (17) which were analysed for authorship pattern with his 68 collaborators. The most active researchers having number of publications with Ketterle were: S. Inouye (26), A. P. Chikkatur (20), M. R. Andrews (19), D. M. Stampur-Kurn (18), D. S. Durfee (17), H. J. Miesner (17) and D. E. Pritchard (17). His productivity coefficient was 0.78 which clearly indicates that his productivity increased after 50 percentile age. The highest collaboration coefficient (1) for Ketterle was found in 1983-1985, 1988, 1991-1995, and 2001. The publication concentration was 5.21% and publication density was 2.01. The core journals publishing his papers were: Phys. Rev. Lett. (30), Applied Physics-B (7), Journal of Chemical Physics (5), Nature (5), Physics Review-A (5), and Science (5). Most prolific keywords in titles were: Bose-Einstein condensate (38), Bose-Einstein condensation (15), Observation (9), Helium hydride (8), Emission spectrum (6) and Suppression (4). ‘Bio-bibliometrics’ is a method of retrieving and visualizing biological information that uses co-occurrence of gene naming terms in Medical Sciences to generate semantic links between genes. Therefore it is suggested that ‘Scientometric Portrait’ is the appropriate phrase for the studies on scientists and ‘Informetric Portrait’ for the studies pertaining to researchers in other disciplines such as arts, humanities, and social sciences